WAYS TO MAKE MEANING IN UZBEK LANGUAGE - Nurmanov F. I. (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the problem of meaning in Uzbek linguistics, the semantic structure of the word, the processes that take place in this structure, the importance of various changes in the structure of the text.